Association between serum arginine levels and cancer risk: A community-based nested case-control study - Liu, Tong; Wang, Xiaomeng; Jia, Pingping; Liu, Chenan; Wei, Yaping; Song, Yun; Li, Shuqun; Liu, Lishun; Wang, Binyan; Shi, Hanping (Frontiers in Nutrition, 2022)
Objective: The effect of arginine on tumors appears to be bidirectional. The association of serum arginine with the risk of incident cancer remains uncovered at present. We aimed to investigate the prospective relationship of baseline serum arginine concentrations with the risk of incident cancer in hypertensive participants. Methods: A nested, case-control study with 1,389 incident cancer cases and 1,389 matched controls was conducted using data from the China H-Type Hypertension Registry Study (CHHRS). Conditional logistic regression analyses were performed to evaluate the association between serum arginine and the risk of the overall, digestive system, non-digestive system, and site-specific cancer. Results: Compared with matched controls, cancer patients had higher levels of arginine (21.41 μg/mL vs. 20.88 μg/mL, p<0.05). When serum arginine concentrations were assessed as quartiles, compared with participants in the lowest arginine quartile, participants in the highest arginine quartile had a 32% (OR=1.32, 95% CI: 1.03 to 1.71), and 68% (OR=1.68, 95% CI: 1.09 to 2.59) increased risk of overall and digestive system cancer, respectively, in the adjusted models. In the site-specific analysis, each standard deviation (SD) increment of serum arginine was independently and positively associated with the risk of colorectal cancer (OR=1.35, 95% CI: 1.01 to 1.82) in the adjusted analysis. Conclusions: We found that hypertensive individuals with higher serum arginine levels exhibited a higher risk of overall, digestive system, and colorectal cancer.